Comparative Analysis of Public Relations Roles, Practitioners’ Functions and Communication Models in Public and Private Organizations in Nigeria - Nsini Eyo (LSPR Institute of Communication & Business, 2026)
The study comparatively examines Public Relations roles, practitioner functions and communication models as practiced in public and private organizations in Nigeria. The main objetive of the study is to investigate the roles of public relations practitioners in public and private organizations in Nigeria, with a focus on Akwa Ibom and to identify the communication models adopted within these establishments. Using a qualitaive design, data were collected through face-to-face semi structured interviews with 22 purposively selected senior PR professionals, including communication managers, directors and Public Relations managers. Interview questions were guided by the study's objectives, review of literatures and Structuration Theory to facilitate the interview process. Data from interviews were transcribed, coded, and thematically analyzed using Atlas ti, 8 software. Thematic analysis revealed that Public Relations facilitates stakeholders engagement and crisis management in both sectors, public sector organizations tend to adopt reactive strategies, with practitioners performing mainly technician roles, whereas private organizations employ proactive approaches with practitioners performing dual roles involving technician and managerial responsibilties. Further finding revealed public sector organizations rely mainly on linear, one-way communication for operational purposes, whereas private organizations apply transactional two-way model that promotes feedback, participation and strategic alignment of PR. The study further highlights how leadership style, organizational culture and power dynamics shapes PR effectiveness. The paper recommends empowering PR professionals and granting autonomy to the Nigerian Institute of Public Relations to regulate the profession without interference , as well as promoting the integration and acceptance of PR into strategic management in the country.